Risk compensation & optimistic bias in condom use and HIV prevention - Esperal, Zohra Jane T.
Seafarers are vulnerable to HIV. They were among those who were found to be vulnerable to contracting the HIV since they are highly mobile and they are often away from their families and partners for prolonged periods of time (Earnest & Finger, 2006). This is a cross-sectional analytic study. The respondents are composed of 449 males seafarers who have female sex partners. The study explored the possibility of risk compensation and optimistic bias happening in condom use and HIV prevention. Risk compensation was explored by determining the association of condom use and type of sexual encounter of Filipino seafarers. The result of the study shows that among married seafarers, those who used condom were 26 time more likely to engage in non-regular and/or multiple sexual partners (or risky sexual encounter) (OR = 25.7, CI (95%) 12.40 and 53.15) compared to those who did not use condom. Among single seafarers, those who used condoms were 5 times among likely to engage in risky encounter (PR=5.3 (95%_ 2.2 ? 12.64) compared to those who did not use condom. The study also determined if seafarers are optimistically biased by first looking into the association of seafarer?s type of sexual encounter and their perceived risk for HIV. The association between type of sexual encounter and perceived risk for HIV is modified by level of knowledge about HIV. The result of the study shows that among seafarers who had good knowledge about HIV and who still engage in non-regular and/or multiiple sexual partners (or risky sexual encounter) were six times more likely to perceived themselves at risk for HIV (OR ? 5.5, CI (95%) 1.78 ? 17.06) compared to seafarers with one regular partner. Among seafarers who had poor knowledge on HIV, those who engaged in non-regular and/or multiple sexual encounters (or risky sexual encounter) were two times more likely to perceive themselves at risk for HIV (OR = 1.52, CI (95%) 0.88 ? 2.62) compared to seafarers with one regular partner. The non significance of the result can be explained by the inadequate sample size. The computed power of the test for this objective was only 65%. Lastly, the study tried to determine if the actual behavior of seafarers matched their perception of risk for HIV through McNemar?s Test. The result shows that there is no discrepancy between Filipino seafarer?s type of sexual encounter and their perception of risk (p= 0.15). This means that there is absence of optimistic bias. This study suggests the possibility that condom use among seafarers may drive them to engage in non-regular and/or multiple sexual partners (or risky sexual encounter) because of the phenomenon of risk compensation. Seafarers may perceive that since they use condom they are protected and can engage in risky sexual behavior. As indicated in the above-mentioned result, the study shows that seafarers with good knowledge about HIV were not optimistically biased in their perception of risk for HIV. However, the researcher recommends that further studies be done to confirm the absence or existence of optimistic bias among filipino seafarers because of the small sample size and low power of the test the true relationship between the variables risky sexual encounter and perceived risk for HIV may have not been captured.
Thesis--(Master of Science in Epidemiology-Public Health) University of the Philippines Manila, 2013
Keywords: Sexual behavior; Condom use; HIV infections--prevention and control